Genome-wide identification of actin-depolymerizing factor family genes in melon (Cucumis melo L.) and CmADF1 plays an important role in low temperature tolerance - Lv, Yanling; Liu, Shihang; Zhang, Jiawang; Cheng, Jianing; Wang, Jinshu; Wang, Lina; Li, Mingyang; Wang, Lu; Bi, Shuangtian; Liu, Wei; Zhang, Lili; Liu, Shilei; et al. (Frontiers in Plant Science, 2024)
Actin depolymerizing factors (ADFs), as the important actin-binding proteins (ABPs) with depolymerizing/severing actin filaments, play a critical role in plant growth and development, and in response to biotic and abiotic stresses. However, the information and function of the ADF family in melon remains unclear. In this study, 9 melon ADF genes (CmADFs) were identified, distributed in 4 subfamilies, and located on 6 chromosomes respectively. Promoter analysis revealed that the CmADFs contained a large number of cis-acting elements related to hormones and stresses. The similarity of CmADFs with their Arabidopsis homologue AtADFs in sequence, structure, important sites and tissue expression confirmed that ADFs were conserved. Gene expression analysis showed that CmADFs responded to low and high temperature stresses, as well as ABA and SA signals. In particular, CmADF1 was significantly up-regulated under above all stress and hormone treatments, indicating that CmADF1 plays a key role in stress and hormone signaling responses, so CmADF1 was selected to further study the mechanism in plant tolerance low temperature. Under low temperature, virus-induced gene silencing (VIGS) of CmADF1 in oriental melon plants showed increased sensitivity to low temperature stress. Consistently, the stable genetic overexpression of CmADF1 in Arabidopsis improved their low temperature tolerance, possibly due to the role of CmADF1 in the depolymerization of actin filaments. Overall, our findings indicated that CmADF genes, especially CmADF1, function in response to abiotic stresses in melon.